Depth Of The Curve Of Spee In Relatıon To Dental Class And Vertıcal Skeletal Pattern - Münire Ece Sabah; Gökhan Önçağ (Galenos Yayinevi, 2002)
The aim of the present study is to evaluate the changes in the depth of the curve of Spee in relation to dental class and vertical skeletal pattern. 90 patients with no previous record of orthodontic treatment were grouped according to their malocclusion and vertical skeletal pattern. The depth of the curve of spee was determined on the study models and the groups were compared statistically. The results of this study show that there is a significant difference between the Angle malocclusion groups regarding the depth of the curve of Spee, Class III malocclusions being systematically lower than that of the other two classes. However no significant difference was detected in relation to the vertical skeletal parameter.